Prevalence of Hate Crimes and Hate Incidents in Municipalities in North Macedonia: Olga Kosevaliska, Zhaneta Poposka, Elena Maksimova - Meško, Gorazd; Kutnjak Ivković, Sanja; Hacin, Rok (The UN Sustainable Development Goals and Provision of Security, Responses to Crime and Security Threats, and Fair Criminal Justice Systems, 2024)
The chapter aims to explore the potential correlation between specific types of hate crimes and their occurrence in various municipalities throughout the Republic of North Macedonia. Geovisualisation techniques are employed to map these hate crimes and analyse their characteristics based on various factors. The results showed that hate crimes are a critical issue in North Macedonia, affecting various regions in the country. The Skopje Region records the highest number of hate crimes based on ethnicity and political beliefs, indicating a dire need for law enforcement to play a more preventive role. Meanwhile, cities near the border primarily experience hate crimes based on migrant status, which calls for increased police patrols in “hotspots” to prevent potential attacks. The high rate of ethnic-based hate crimes in municipalities with significant ethnic representation and political-based hate crimes during election periods also require proactive policing measures.